Problem based learning e-handout: Improving students’ mathematical representation and self efficacy - Rahmawati, Dwi Ulan; Wilujeng, Insih; Jumadi, Jumadi; Kuswanto, Heru; Sulaeman, Nurul F; Astuti, Dwi Puji (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2020)
This research aimed to improve students’ ability in mastering mathematical representation and self-efficacy in an optical material. The pre-experimental design was implemented as the research method by one group pre-test and post-test. The samples were selected by implementing a cluster random sampling technique. The sample consisted of the eleventh-grade Science students with a total number of 54 in SMAN 1 Sleman. The students’ ability in mathematical representation was measured by using pre-test and post-test in the form of an essay test. Students’ self-efficacy was measured by using a questionnaire as the research instrument. The data were analyzed using the Wilcoxon test and descriptive analysis to determine the N-Gain score and self-efficacy was calculated by using percentages. The results revealed that the PBL E-Handout supported by PhET simulation using Schoology could improve students’ mathematical representation abilities and self-efficacy. This is indicated by the value of Asymp Sig. (2-tailed) smaller than 0.05 where 0.000<0.05 and the N-Gain score is 0.3 in the intermediate category